Pertinent internal and external issues in industrialised building system (IBS) construction business in Malaysia / Vivian Anne Thomas Tarang ... [et al.] - Thomas Tarang, Vivian Anne; Mohammad, Mohammad Fadhil; Nizam Akbar, Anis Rosniza; Mohamed, Mohamed Rizal (UiTM Press, 2022)
Industrialised Building System (IBS) construction business has emerged as one of the potential business ventures as the Malaysian construction industry is in a constant need to shift from conventional method of construction to IBS adoption aligning to Construction 4.0 Strategic Plan 2021-2025 and The National Entrepreneurship Policy 2030 (NEP 2030). In line with boosting the IBS implementation, a brief exploratory study has been conducted to validate several IBS construction business issues among IBS contractors in Malaysia, internally and externally. From selected online databases such as Google Scholar, Scopus and Web of Science, 397 articles were extracted from the "Industrialised Building System (IBS) Issues in Malaysia" keywords. A set of semi-structured questionnaires was developed and pre-tested before flowing it to 25 respondents from different backgrounds in construction business related to IBS. Internally, it is discovered that the easy access to cheap labours, substantial start-up capital and ineffective IBS knowledge transfer among construction players are internal challenges that IBS contractors must endure. Concurrently discovered, IBS contractors are externally challenged by heavy Chinese-led and big boys construction project monopoly, government's weak push for IBS technology, securing smooth payment delivery, and the unstable political climate in the Malaysian political scenarios. This paper aims to validate and outreach the challenges IBS contractors face internally and externally to strategize the business plan systematically.